Experimentally Induced Biliary Atresia by Means of Rotavirus‐Infection Is Directly Linked to Severe Damage of the Microvasculature in the Extrahepatic Bile Duct. Issue 5 (22nd November 2018) - Oetzmann von Sochaczewski, Christina; Pintelon, Isabel; Brouns, Inge; Thys, Sofie; Deigendesch, Nikolaus; Kübler, Joachim F.; Timmermans, Jean‐Pierre; Petersen, Claus
ABSTRACT: Vascular damage has been reported to contribute to atresia formation in several diseases including biliary atresia. This study focused on the extrahepatic biliary plexus in experimental biliary atresia. Newborn BALB/cAnNCrl‐pups were infected with rhesus rotavirus within 24 hr after birth to induce experimental biliary atresia. The extrahepatic biliary plexus was examined by confocal microscopy on whole‐mount preparations, scored by three independent researchers, and further evaluated at the subcellular level with transmission electron microscopy. Imaging results revealed a progressive destruction of the extrahepatic biliary vascular plexus in the course of experimental biliary atresia induced by rotavirus infection. Endothelial cell damage was already visible as cell swelling and necrosis in the first days after infection and a damaged microcirculation that rapidly deteriorated with progression of obliterative cholangiopathy, was observed in the infected mice as early as 72 hr after birth. In experimental biliary atresia, the destruction of the extrahepatic biliary vascular plexus starts already in the first days postinfection and clearly precedes the morphological symptoms of atresia. The deterioration of the vascular bed architecture continues with disease progression. Therefore, we conclude that the (ultra)structural changes in the extrahepatic biliary microvasculature occurring before the visible onset of atresia has a predictive diagnostic value and this impairment in blood supply to the extrahepatic bile duct may be an important contributing factor to the pathogenesis of acquired biliary atresia. Anat Rec, 2018. © 2018 Wiley Periodicals, Inc. Anat Rec, 302:818–824, 2019. © 2018 Wiley Periodicals, Inc.